The World Book encyclopedia. - World Book, Inc. (Chicago : World Book, 2008)
"A 22-volume, highly illustrated, A-Z general encyclopedia for all ages, featuring sections on how to use World Book, other research aids, pronunciation key, a student guide to better writing, speaking, and research skills, and comprehensive index"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Encyclopedias and dictionaries